Cover Feature: Copper‐Catalyzed Synthesis of Trinuclear N‐Fused Hybrid Scaffolds by Double C(sp2)–N Bond Formation between 2‐(2‐Bromoaryl)indoles and 2‐Aminoazoles (Eur. J. Org. Chem. 19/2020). Issue 19 (13th May 2020) - Diep, Thi Duyen; Duy Quang Dao, Pham; Ho, Son Long; Cho, Chan Sik
Abstract : The Cover Feature shows a copper‐catalyzed construction of trinuclear N‐fused hybrid scaffolds, indole/benzimidazole/quinazoline and indole/imidazole/quinazoline, by the reaction of 2‐(2‐bromoaryl)indoles with 2‐aminoazoles under microwave irradiation. The reaction pathway seems to proceed via double C( sp 2 )‐N bond formation accompanied by ammonia evolution between 2‐(2‐bromoaryl)indoles and 2‐aminoazoles. The background picture is "The ARC" (Architecture of River Culture, a cultural center communicating with rivers), a remarkable architecture symbolizing the harmony of river and nature which looks similar to a microwave reactor, near Nakdong River in Daegu, Republic of Korea. More information can be found in the Full Paper by C. S. Cho et al.